2019
DOI: 10.1073/pnas.1901120116
|View full text |Cite
|
Sign up to set email alerts
|

Fast-moving bat ears create informative Doppler shifts

Abstract: Many animals have evolved adept sensory systems that enable dexterous mobility in complex environments. Echolocating bats hunting in dense vegetation represent an extreme case of this, where all necessary information about the environment must pass through a parsimonious channel of pulsed, 1D echo signals. We have investigated whether certain bats (rhinolophids and hipposiderids) actively create Doppler shifts with their pinnae to encode additional sensory information. Our results show that the bats' active pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…Building on these prior findings, more recent analyses have demonstrated that the timevariant effects can enhance sensory-coding capacity and the ability to determine the direction of a sound source [59,60]. Researchers experimentally replicated the fast ear motions of the horseshoe bat pinna, and recorded CF signals emitted from different azimuth and elevation angles with respect to the receiver [60]. Their results demonstrated direction-dependent Doppler shifts in the received signals, and this finding suggested that the Doppler shifts due to this pinna motion can potentially aid in direction finding [60].…”
Section: Dynamics Of Auditory Peripherymentioning
confidence: 91%
See 2 more Smart Citations
“…Building on these prior findings, more recent analyses have demonstrated that the timevariant effects can enhance sensory-coding capacity and the ability to determine the direction of a sound source [59,60]. Researchers experimentally replicated the fast ear motions of the horseshoe bat pinna, and recorded CF signals emitted from different azimuth and elevation angles with respect to the receiver [60]. Their results demonstrated direction-dependent Doppler shifts in the received signals, and this finding suggested that the Doppler shifts due to this pinna motion can potentially aid in direction finding [60].…”
Section: Dynamics Of Auditory Peripherymentioning
confidence: 91%
“…Building on these prior findings, more recent analyses have demonstrated that the timevariant effects can enhance sensory-coding capacity and the ability to determine the direction of a sound source [59,60]. Researchers experimentally replicated the fast ear motions of the horseshoe bat pinna, and recorded CF signals emitted from different azimuth and elevation angles with respect to the receiver [60].…”
Section: Dynamics Of Auditory Peripherymentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies have shown that humans and other animals change the rate and force of inhaling based on the presence of odors. Many animals turn their heads, or even alter the position or shape of their ears, in order to use that alteration in order to gain specific information about the incoming sound for localization and recognition (for an example, see Yin & Müller, 2019). A particular example is the star-nosed mole that haptically senses potential prey by a specialized nose organ (Catania, 2011).…”
Section: An Active-vision Interpretation Of Preview Effectsmentioning
confidence: 99%
“…Different bat species utilize a variety of actions to enhance sonar localization. Bats in the Rhinolophid and Hipposiderid families move the pinnae rapidly in the anterior and posterior directions during call production and reception [ 5 ]. These movements of the pinnae create interaural intensity differences and Doppler shifts in the constant frequency (CF) signals used by these bat species, which help them localize sound sources, particularly in the vertical plane [ 6 ].…”
Section: Introductionmentioning
confidence: 99%